Manajemen Kemitraan dalam Peningkatan Mutu Lulusan Diploma Tiga Kebidanan - Nani Yunarsih (Faletehan Health Journal, 2020)
The increasing number of midwifery colleges has not been matched with the quality due to lack of facilities and infrastructure to support clinical practices. The purpose of this study was to identify: 1) the purpose of partnership, 2) partnership program, 3) implementation of partnership program, 4) problems and challenges faced in partnership, 5) further improvement steps, and 6) qualities of partnership graduates. The object of this study were Aisyiah Midwifery Academy, Dr Drajat Prawiranegara Hospital, Bina Husada Midwifery Academy, and Kencana Hospital. Data were collected through observations, interviews and documentation study. Research results showed that: 1) the purposes of partnership in improving the quality of education and the quality of graduate competence, establishing long-term partnerships and implementing threefold missions of higher education, have the form of midwifery partnership activities and competency support training, 2) the implementation of partnership still needs improvement starting from organizing to partnership strategies, 3) partnership issues and challenges in the management and leadership implementation, 4) further improvement steps including management, activities, budget, human resources, other related parties, and partnership. This study recommended lecturers to be able to alocate their time for academic duties and student coaching duties and midwifery colleges to plan operational strategies in collaboration.